1979
DOI: 10.1128/aac.16.6.813
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities, nephrotoxicity, and ototoxicity of a new aminoglycoside, Win 42122-2

Abstract: Win 42122-2 is a new aminoglycoside antibiotic obtained from a mutant strain of Micromonospora purpurea. In vitro and in vivo comparisons of Win 42122-2 with gentamicin and amikacin revealed that Win 42122-2 generally was less active than gentamicin against Pseudomonas and many Enterobacteriacae, especially Klebsiella and indole-negative Proteus. Against most gentamicin-susceptible isolates, Win 42122-2 was more active than amikacin. Gentamicin-resistant clinical isolates were usually resistant to Win 42122-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is a complex of 2-hydroxygentamicin Cl (55%), C2a (10%), and C2 (35%), which is less active in vitro than gentamicin (GM) and generally inactive against GMresistant bacteria. However, it appears to be less toxic than GM in rats, guinea pigs, and cats (3). The reduced toxic potential of WIN may be greater than its reduced in-vitro potency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a complex of 2-hydroxygentamicin Cl (55%), C2a (10%), and C2 (35%), which is less active in vitro than gentamicin (GM) and generally inactive against GMresistant bacteria. However, it appears to be less toxic than GM in rats, guinea pigs, and cats (3). The reduced toxic potential of WIN may be greater than its reduced in-vitro potency.…”
mentioning
confidence: 99%
“…However, comparative toxicological studies in a variety of animal species suggested that WIN was significantly less toxic than GM. Furthermore, the magnitude of the difference in toxicity was generally greater than the difference in potency (3). The development of a GM-like aminoglycoside with significantly reduced potential for toxicity would clearly be advantageous, especially for the treatment ofsevere disease due to gram-negative bacilli and infections that require long-term therapy, such as enterococcal endocarditis and the mycobacterioses.…”
mentioning
confidence: 99%